The use of warm-up activities in motivating 10th form students to learn reading skill = Sử dụng các hoạt động khởi động trong bài dạy đọc hiểu nhằm nâng cao hứng thú học kỹ năng đọc hiểu cho học sinh lớp 10. - Nguyễn, Thị Tuyết Nhung (University of Languages and International Studies, 2017)
How to teach and learn English effectively is a big concern of most teachers and language students. Many students at Kien An High School find it boring to study reading lessons. This study is intended to investigate the use of warm-up activities and their effects on the 10thform students at Kien An High School and to make some suggestions to improve the quality of learning reading lessons. The study was conducted to answer the questions: What are warm-up activities? Are warm-up activities an effective technique for motivating 10thform students to learn reading skill? The author took a sample of 94 students at Kien An High School. Data from the questionnaires was analyzed quantitatively and qualitatively